Foods of plant origin. Multimethod for the determination of pesticide residues using GC- or LC-based analysis following acetonitrile extraction/partitioning and cleanup by dispersive SPE. Validation data of the modular QuEChERS-method. (30th April 2017) - British Standards Institution,
No abstract available